2016
DOI: 10.1017/s0022215116000311
|View full text |Cite
|
Sign up to set email alerts
|

Early stage squamous cell carcinoma of the lower lip: predictive factors for recurrence

Abstract: Surgical margin control is important to prevent local recurrence, especially in thicker tumours. In addition, neck metastasis is rare in early stage lower lip squamous cell carcinoma. A 'wait and see' policy might be preferred in early stage T1 lower lip squamous cell carcinoma cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…1,3 OTSCC exhibits an aggressive biological behavior and has usually a poorer prognosis when compared to tumors at other sites. 4,5,6,7 Lower lip squamous cell carcinoma (LLSCC) is more common among male patients above the age of 50 years and solar radiation is the main etiological factor. 7 LLSCC is usually associated with a good prognosis and low mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 OTSCC exhibits an aggressive biological behavior and has usually a poorer prognosis when compared to tumors at other sites. 4,5,6,7 Lower lip squamous cell carcinoma (LLSCC) is more common among male patients above the age of 50 years and solar radiation is the main etiological factor. 7 LLSCC is usually associated with a good prognosis and low mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for regional recurrence in head and neck SCC have been widely evaluated. Fang et al [ 16 ] reported that the differentiation degree significantly affected the locoregional control in buccal SCC, and Ozkul et al [ 9 ] described tumor thickness as being positively correlated with recurrence; perineural invasion and invasion depth were also predictors for regional metastasis. [ 10 , 17 ] However, few authors have described the possible factors affecting regional metastasis in upper lip SCC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 8 ] A number of variables, including tumor stage, perineural invasion, tumor subsite, and differentiation extent, have been described as being associated with the chance of mortality in head and neck SCC. [ 9 , 10 ] It is widely accepted that lymphatic metastasis is the most important factor in determining prognosis, and the survival rate can be reduced by 50% if there are cervical positive pathological nodes found at diagnosis. Although both Luna-Ortiz et al [ 5 ] and Zitsch et al [ 8 ] reported the apparent association between lymph node metastases and clinical-pathologic variables such as tumor stage and tumor differentiation, the detailed prognostic factors for lymphatic metastasis still remain unclear in upper lip cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Five-year survival rates are defined as the main attribute that describes the long-term prognosis of the tumour. Studies have reported that the five-year survival rate of lower lip cancer with cancer T stage of I to varies from 68.3% to 84.5%, with some studies drawing a direct link to pre-cancerous process of actinic cheilitis (Schüller et al, 2015;Ozkul et al, 2016). Pathology-associated death in case of lower lip cancer is usually due to metastatic tumorous formations in physiologically crucial neck organs.…”
mentioning
confidence: 99%